Measuring satisfaction on augmented reality courseware for hearing-impaired students: adjustment formula form system usability scale / Norziha Megat Mohd Zainuddin, Nurazean Maarop and Wan Azlan Wan Hassan - Mohd Zainuddin, Norziha Megat; Maarop, Nurazean; Wan Hassan, Wan Azlan (Universiti Teknologi MARA, 2022)
Satisfaction is an important usability attribute in developing a courseware which involves end users. Measuring satisfaction among hearing-impaired students is different than measuring it among common students because they learn using sign language and have different learning styles. An educational courseware for hearing-impaired students is employed to measure this. The courseware uses the Augmented Reality technology and it is called PekAR-Mikroorganisma. Hence, this article focuses on the methodology of measuring and the attributes that contribute to users’ satisfaction. An adaptation of the System Usability Scale was used to identify the satisfaction value. Fifteen hearingimpaired students were employed as a case study. Findings show that the average satisfaction value of SUS in using PekAR Mikroorganisma is 87.8 per cent, and it consider as high or B grade. It is hoped PekAR-Mikroorganisma can help the hearing-impaired to understand lessons better through the enhancement of their comprehension on abstract concepts. The teaching and learning using AR able to assure equity in education for the students in understanding certain topics. The study suggested the used of AR for hearing-impaired students for various level up to the higher education.